Asuhan Keperawatan Pada Pasien Dengangastroenteritis Akut (GEA) Di Ruangan Muzdalifah Rumah Sakit Aisyiyah Pariaman - Yosi Andini Simatupang; Kheniva Diah Anggita; Aulia Asman; Linda Marni (CV. ITTC INDONESIA, 2026)
Acute gastroenteritis (GEA) remains a common health problem with a high morbidity rate, both globally and nationally. Based on World Health Organization (WHO) data, gastroenteritis causes millions of cases each year and can lead to serious complications such as dehydration and electrolyte imbalances. In Indonesia, the prevalence of acute gastroenteritis is approximately 6.8%, while in West Sumatra it reaches 8.5%. Data from Aisyiyah Pariaman Hospital indicate that gastroenteritis is among the top ten diseases, with an increasing trend in cases from 43 cases in 2023 to 90 cases in 2025. This condition shows that gastroenteritis remains a significant health problem requiring optimal management, particularly related to hygiene, dietary patterns, and environmental factors.The purpose of this case study is to understand and apply comprehensive nursing care for patients with gastroenteritis. The method used is a case study approach based on the nursing process, including assessment, diagnosis, intervention, implementation, and evaluation of patients in the Muzdalifah Ward at Aisyiyah Pariaman Hospital.The results show that patients with gastroenteritis generally experience diarrhea, nausea, vomiting, abdominal pain, and signs of dehydration such as decreased skin turgor and dry mucous membranes. The main nursing diagnoses include diarrhea, hypovolemia, hyperthermia, and risk of electrolyte imbalance. Interventions implemented, such as diarrhea management, fluid monitoring, rehydration therapy, and health education, have been shown to improve the patient’s condition.In conclusion, appropriate and comprehensive nursing care is essential in managing patients with gastroenteritis to prevent complications. It is recommended that healthcare providers enhance education on hygiene and healthy dietary habits, as well as strengthen patient monitoring to reduce the incidence of gastroenteritis.